The Rise of State Capital Transforming Markets and International Politics - Babić, Milan (Comparative Political Economy, 2023)
The past two decades have seen a rapid rise in large-scale, state-led transnational investment from countries as different as China, Norway and Russia. By bundling economic resources, these countries have entered global markets through massive state-led investments. This transformation of states into global economic actors is historically unprecedented and presents a major challenge for how states relate to each other in the international system. Milan Babic examines how states have become major corporate owners in the global economy and unpacks the lasting effects of this on our understanding of the state and international politics. Drawing on research into the largest firm-level dataset on state ownership to date, in combination with in-depth historical and conceptual analysis, the book offers a comprehensive analysis of the rise of the state in the global economy and its present and future consequences for international relations.